An Analysis of Figurative Language in Thomas Gray’s ‘Elegy Written in a Country Churchyard’ - Adha, Ruly (JL3T (Journal of Linguistics, Literature and Language Teaching), 2024)
Figurative language is one of intrinsic elements of a poem. The use of figurative language is intended to beautify expressions or sentences. The purpose of this research was to describe the types of figurative languages used by Thomas Gray in his poem ‘Elegy Written in a Country Churchyard’. The researcher used a qualitative descriptive approach. The object of this research was Gray’s poem ‘Elegy Written in a Country Churchyard’. Documentation was the instrument in collecting the data. The documentation was taken from Gray’s poem entitled ‘Elegy Written in a Country Churchyard’. After reading the poem, the researcher selected figurative languages in all stanzas. Then, the researcher identified the types of figurative language and described the meaning. As the result, the researcher found that there were some figurative languages found in Gray’s poem, namely personification (17 data), transferred epithet (1 datum), metonymy (2 data), onomatopoeia (1 datum), inversion (7 data), interrogation (2 data), hyperbole (2 data), and euphemism (4 data). From the data, personification was the figurative language that mostly found in the poem ‘Elegy Written in a Country Churchyard’ Written by Thomas Gray.